Borderland Child Heterotopias. A Case Study on the Belgian-German Borderlands - Venken, Machteld (Journal of Borderlands Studies, 2021)
Abstract: „This article investigates the capacities of children to participate actively in their lives in the Belgian-German borderlands in the time period between World War I and World War II. The article interprets a body of historical sources that has hitherto been left unexplored – namely, borderland child ego documents – with the help of insights from child studies and border studies. These ego documents unfold as borderland child heterotopias. Borderland child heterotopias include material places and creative linguistic loci established by or for those considered in crisis in relation to the rest of society based on their age within or outside child spaces of modernity. The borderland child heterotopias offer a unique gateway to borderland children’s past imaginations for a better world.“
Keywords: Grenzgebiet; Kind; Sozialraum

Cross-border residential mobility of people working in Luxembourg. Developments and impacts - Nienaber, Birte; Pigeron-Piroth, Isabelle (European Borderlands. Living with Barriers and Bridges, 2017)
Keywords: Grenzarbeitnehmer; Sozialraum